Introducing Transcultural Nursing Education: Implementation of Transcultural Nursing in the Postgraduate Nursing Curriculum. (12th February 2015) - Prosen, Mirko
Abstract: Patients are entitled to culturally competent care. Nurses must be prepared to recognize patients' needs that derive from their culture and to develop skills that will facilitate their achievement. Nursing curricula therefore need to include a cultural content and student nurses need to be culturally competent. The aim is to use cultural knowledge to deliver culturally sensitive and congruent care. Transcultural nursing education does not exist as a course in undergraduate or postgraduate nursing programs in Slovenia. In an effort to advance the diversity of elective courses in the postgraduate nursing program at the Faculty of Health Sciences of the University of Primorska, we tried to develop and introduce transcultural nursing into the existing curriculum. The aim of the paper is to outline the development of transcultural nursing content as it was set in the course curriculum and planned teaching and learning approaches.